Nghiên cứu ảnh hưởng của nanosilica đến tính chất cơ học của màng polyme polyurea trên cơ sở polyaspartic este desmophen NH1520 đóng rắn bằng Desmodur N3600 - Huy Cường, Huỳnh Lê; Diệu, Trần Vĩnh; Thành, Nguyễn Đắc; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2016)
The effects of silica nanoparticles (nanosilica) to mechanical properties of polymer coating film polyurea based on polyaspartic ester resin Desmophen NH1520 and hardener Desmodur N3600 have been studied. Surface modification of nanosilica was realized by 3-amino propyl triethoxy silan (APTES). Dispersions of nanosilica in polyaspartic ester resin Desmophen NH1520 were carried out by stirring and ultrasonic vibration. The structures of the hybrids were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The thermal properties were characterized by thermo gravimetric analysis (TGA). The results show that nanosilica is good dispersed and improved mechanical properties of polymer coating film polyurea based on polyaspartic ester resin Desmophen NH1520. Keywords. Polyurea resin, polyaspartic ester resin Desmophen NH1520, silica nanoparticles, nanosilica, modified nanosilica.